Potensi Fluktuasi Harga Komoditas Pertanian dan Dampaknya di Provinsi Banten - Tatang Sutisna; Aulia Ikhsan; Siti Widiati; Ari Tresna Sumantri; Gugun Gunawan (JURNAL AGRIBISNIS TERPADU, 2023)
The impact of price fluctuations on producers is an important aspect that must be considered in the agricultural fam business. This research aims to analyze how potential producers are affected by price fluctuations in red chilies, curly chilies, and shallots. This research uses a descriptive analysis of commodity prices throughout the observation period using time series charts. Inferential quantitative risk measurement analysis uses the Value at Risk (VaR) Historical Simulation method. The research results show that at the beginning of 2020, the price of red chilies peaked while the price of shallots reached its lowest point. This pattern occurred again at the beginning of the following year, but in the second year of observation, cayenne pepper became the commodity with the highest price. Producers and consumers of the cayenne pepper commodity have a relatively more significant risk than producers and consumers of the other two commodities. From the producer's perspective, the chances that arise are caused by fluctuations in sales prices, which cause profit decrease concerns. Increasing prices results in additional costs outside of financial planning, thus becoming a risk factor for consumers.Keywords: price fluctuations, strategic food commodities, Value at Risk, Historical Simulation